2022
DOI: 10.3389/fmars.2022.853104
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Foraging Habitats of Sympatrically Breeding Gadfly Petrels in the South Pacific Ocean

Abstract: Gadfly petrels (genus Pterodroma) are one of the most threatened groups of birds. They are exceptionally well adapted to forage over enormous areas to maximize chances of encountering prey. Their wide-ranging travel, extensive use of oceanic habitats beyond national jurisdictions (the high seas), and limited information on their at-sea distributions and foraging ecology pose several management challenges. Here, we examined the foraging distributions and habitat preferences of three gadfly petrels that breed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…We analysed movement data, activity patterns and diving behaviour to quantify fine scale at-sea behaviours of incubating Bermuda petrels. Similar to previous studies [16, 31], GPS tracking showed that Bermuda petrels undertook extended foraging trips to the NNE of Bermuda, apparently targeting the path of the Gulf Stream, and confirming a reliance on vast oceanic areas for successful foraging as in other Pterodroma petrels [14, 16, 49, 50]. However, in contrast to many other Procellariiformes [10, 27], which can perform dives of considerable duration and depth (see references in [28, 51]), our TDR data suggest that the Bermuda petrel is a surface feeder with limited capacity to dive.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We analysed movement data, activity patterns and diving behaviour to quantify fine scale at-sea behaviours of incubating Bermuda petrels. Similar to previous studies [16, 31], GPS tracking showed that Bermuda petrels undertook extended foraging trips to the NNE of Bermuda, apparently targeting the path of the Gulf Stream, and confirming a reliance on vast oceanic areas for successful foraging as in other Pterodroma petrels [14, 16, 49, 50]. However, in contrast to many other Procellariiformes [10, 27], which can perform dives of considerable duration and depth (see references in [28, 51]), our TDR data suggest that the Bermuda petrel is a surface feeder with limited capacity to dive.…”
Section: Discussionsupporting
confidence: 83%
“…Bermuda petrels foraged thousands of kilometers away from the breeding colony (average 1200 km) spending on average 10 days at-sea, similar to other Pterodrom species [14,49,50,52]. They were consistent in their departing direction from the colony, as has been observed in the Murphy's petrels (P. ultima) [49], showing a clear preference for the NNE (Fig.…”
Section: Foraging Trip Directions and Petrel At Sea Distribution Duri...supporting
confidence: 61%
“…It is possible that Snow Petrels spend the majority of their seatime in productive areas where they forage successfully, but this interpretation is limited to nesting birds (a common limitation in seabird tracking studies (Priddel et al, 2014), as those are the individuals accessible to researchers (i.e., juveniles, pre-breeders, and non-breeders are generally not constrained to a nest and are therefore extremely difficult to retrieve from the same location when attaching/detaching tracking devices). State-space modelling of GPS tracking data would allow researchers to identify specific "foraging only" regions [i.e., environmental features actively targeted by the birds; Halpin et al (2022)]. Moreover, with the emergence of circumpolar databases that increasingly provide information on mesopelagic fish species (Woods et al, 2022), and krill (Atkinson et al, 2017), relevant seabird studies whose data overlap with prey data could gain valuable insight on which prey species are most commonly associated with seabird presence.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extreme difficulty of reliably separating Vanuatu Petrels from White-necked Petrels at sea (Shirihai and Bretagnolle 2010), most at-sea records are inferred by proximity to this site, likely underrepresenting the true distribution of the taxon (Figure 1). Recent tracking of provisioning trips by breeding White-necked Petrels from Phillip Island (-29.12, 167.95; one of two current breeding sites for this species) recorded mean “short” trips of 234 km (range Phillip Island 25–433) and 206 km (30–480) and mean “long” trips of 1,063 km (546–2,680) and 810 km (520–1,451) (Halpin et al 2022). It is possible that the Vanuatu Petrel is similar.…”
Section: Distribution Of the Vanuatu Petrelmentioning
confidence: 99%
“…This is a key factor in many seabird breeding colony failures (Ramirez et al 2018). Gadfly petrels are generally less susceptible to this process than other procellariiform species, as they forage over long distances actively searching for prey, rather than targeting specific areas of known high productivity (Halpin et al 2022). With an unknown pelagic range, this process may affect Vanuatu Petrels more acutely than other gadfly petrels.…”
Section: Threatsmentioning
confidence: 99%